KONSEP MAQOMAT DAN AKHWAL - Abdul Wahab Syakhrani; Nadia Nursyifa; Nurul Fithroti (CV. Adiba Aisha Amira, 2024)
Maqamat is the plural form of the word maqam, which literally means rank or degree. In English, maqamat is referred to as stations or stages. Meanwhile, according to the terms of the science of Sufism, maqamat is the position of a servant before Allah, which is obtained through worship, mujahadat and other things, spiritual training and (relationship) that is not broken with Allah SWT. According to Al-Thusi's view, namely: